1988
DOI: 10.1111/j.1939-0025.1988.tb01582.x
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial adaptation of siblings of children with chronic medical illnesses.

Abstract: The behavioral and emotional adjustment of 27 siblings of ill children was compared with that of 27 siblings from "healthy" families. Findings indicated that siblings of ill children had significantly more behavior problems than did controls. Levels of self-concept, however, did not differ. The importance of systemic research on the topic is highlighted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
52
1
7

Year Published

1994
1994
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(66 citation statements)
references
References 30 publications
6
52
1
7
Order By: Relevance
“…Consistent with studies done by Tritt and Esses (1988), siblings who had adequate knowledge about sickle cell disease coped better than those who lacked knowledge, and the extent of knowledge and understanding was not significantly related to age. The siblings who had adequate knowledge seemed to be less anxious and worried, and their ages were varied.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Consistent with studies done by Tritt and Esses (1988), siblings who had adequate knowledge about sickle cell disease coped better than those who lacked knowledge, and the extent of knowledge and understanding was not significantly related to age. The siblings who had adequate knowledge seemed to be less anxious and worried, and their ages were varied.…”
Section: Discussionsupporting
confidence: 91%
“…When asked what they had gained from the experience of having a brother or sister with sickle cell disease, most siblings replied that they had become more patient, compassionate, understanding, helpful, responsible, and sensitive. These benefits are similar to those observed in other siblings by Seligman (1988) and Tritt and Esses (1988). The investigator was even more impressed, however, by those siblings who also reported that they had become more aware of, and knowledgeable about sickle cell disease.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…The focus of the health care professionals, family and friends is on the ill child and parents. In a study by Tritt & Esses (1988) it was the healthy siblings who were identified as the most unhappy members in one-third of families interviewed who had a chronically ill child. Over onehalf of the siblings interviewed believed that the ill child received special treatment.…”
mentioning
confidence: 99%